Biological and Molecular Characterization of Moroccan Isolates of Spiroplasma citri - Tourya Sagouti; Ikram Legrifi; Naima Rhallabi; Zineb Belabess; Moussa El Jarroudi; Said Amiri; Essaid Ait Barka; Abdessalem Tahiri; Rachid Lahlali (Agronomy, 2025)
Spiroplasma citri, a bacterium from the class Mollicutes, is the causative agent of citrus stubborn disease, a serious threat to Moroccan citrus crops, with yield losses reaching 45%. Despite its long-standing presence since 1949 and regulations mandating disease-free citrus plants, data on S. citri in Morocco remain scarce. This study investigates the pathogenicity and symptom variability of Moroccan S. citri isolates using biological indexing and genetic mapping based on the Spiralin and P58 genes. Biological indexing through reverse inoculation revealed that seven out of ten isolates caused moderate to intense symptoms within 8 to 10 weeks, with symptom severity varying across citrus cultivars and regions. These findings suggest variations in pathogen titer. Molecular analysis showed that Moroccan isolates (27GH, 3GH, 8GH, 56MK, 16MK, 60MK, 2GLK, 13SS, and 30S1) exhibited complete (100%) sequence similarity with each other and the reference strain R2-A8. Furthermore, these isolates displayed a high degree of similarity (99.75%) to a Corsican isolate (U13995) and a 94% similarity to an Iranian isolate (KP666137). Analysis of the P58 gene confirmed a high level of homogeneity with Moroccan reference strain R8-A2, closely aligning (99.75%) with the American BR3-3X strain, and 98% similarity to isolates from Syria and Iran. This study lays a foundational insight into the molecular characterization of S. citri in Morocco and provides a groundwork for future research into managing citrus stubborn disease.